White composite packaging adhesive film containing acid barrier layer and application of white composite packaging adhesive film
By introducing an acid-containing barrier layer into the white composite packaging film, the existing white EVA packaging film has solved the problem of high flange and high water vapor transmission during lamination, and a high reflectivity, high adhesion and low water vapor transmission film is achieved, which improves the performance and reliability of the components.
Patent Information
- Application Number
- CN202311183830.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-25
AI Technical Summary
The existing white EVA packaging film is prone to overflow and flange when laminating, causing contamination and coverage of the battery cells, affecting the appearance of the components and power generation efficiency. At the same time, its water vapor transmittance is high, which can easily lead to delamination and corrosion.
A non-precrosslinked white composite encapsulation film containing an acid barrier layer is used, and its structure includes a first acid barrier layer, a high reflective layer and a second acid barrier layer sequentially from top to bottom. The adhesive film improves adhesion and water resistance through the POE layer to avoid the problems of increased hardness and insufficient adhesion caused by pre-crosslinking.
High reflectivity and high adhesion force are achieved, water vapor transmission is reduced, glue overflow, flange and delamination problems are avoided, and long-term reliability of components and photoelectric conversion efficiency are improved.
Smart Images

Figure CN119684912A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells and relates to a white composite packaging adhesive film containing an acid barrier layer and an application thereof, and specifically relates to a non-pre-crosslinked white composite packaging adhesive film containing an acid barrier layer and an application thereof. Background Art
[0002] In recent years, white EVA encapsulation film has been widely used in various types of component products as a mainstream product in the market. As a base film, it can improve the reflectivity, effectively improve the utilization rate of sunlight, and reduce the packaging loss of the component.
[0003] However, due to its own characteristics, white adhesive film is prone to overflow and flanging onto the front solar cell during lamination, causing contamination and coverage of the solar cell, seriously affecting the appearance and power generation efficiency of the module. The industry generally uses pre-crosslinking to partially irradiate the adhesive film before lamination to form a cross-linked network structure to reduce shrinkage during lamination and reduce the probability of overflow and flanging.
[0004] However, this method also has certain disadvantages: the network structure formed by preferential pre-crosslinking increases the hardness of the film at the beginning of lamination to a certain extent, which can easily cause hidden cracks or displacement of the battery cell; furthermore, the degree of pre-crosslinking is generally controlled at more than 30%, and the premature reaction of additives can easily cause insufficient adhesion, which can easily cause delamination between the film and the backplane or the battery cell under humid, hot, ultraviolet and other conditions, resulting in the scrapping of the component.
[0005] Moreover, the introduction of titanium dioxide has weakened the film's ability to isolate water vapor, its volume resistivity and corrosion resistance to a certain extent. However, since it is very susceptible to corrosion by water vapor, polar water molecules will attack the direct van der Waals force or hydrogen bond between the glass and EVA, causing it to fail and lead to delamination. At the same time, water vapor can also cause vinyl acetate to hydrolyze or break under the combination of light and oxygen, forming small molecules such as acetic acid, aldehydes and ketones, which will cause corrosion to the battery cells.
[0006] Therefore, in the art, it is desired to develop a packaging film that has both high reflectivity and low water vapor permeability and can avoid the defects of the existing white EVA packaging film. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a white composite packaging film containing an acid barrier layer and its application, and specifically to provide a non-pre-crosslinked white composite packaging film containing an acid barrier layer and its application. The white composite packaging film provided by the present invention can achieve the high reflectivity of conventional white films and has higher adhesion, and does not require pre-crosslinking, thereby improving production efficiency.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a white composite encapsulation film containing an acid barrier layer, wherein the white composite encapsulation film containing an acid barrier layer comprises, from top to bottom, a first acid barrier layer, a high reflective layer, and a second acid barrier layer stacked in sequence;
[0010] The raw materials for preparing the first acid barrier layer and the second acid barrier layer include the following components: POE particles, a crosslinking agent, silane, a light stabilizer and an antioxidant;
[0011] The raw materials for preparing the high reflective layer include the following components: EVA particles, titanium dioxide, a crosslinking agent, silane, acrylate, a light stabilizer and an antioxidant.
[0012] The white composite encapsulation film provided by the present invention has a high reflective layer which is a non-pre-crosslinked white EVA film, which can effectively improve the reflectivity of the film to light and improve the photoelectric conversion efficiency of the component. The first acid barrier layer and the second acid barrier layer are transparent POE layers, which have the following functions: (1) Compared with the pre-crosslinked white EVA, the POE layer can improve the adhesion between the film and the glass, backplane, and battery cell and maintain it for a long time, thereby reducing the occurrence of component delamination during aging; (2) reducing the phenomenon of battery cell cracking during lamination caused by the hard texture of the pre-crosslinked white film; (3) Because the upper and lower layers of POE film do not contain acidic groups, the free acetic acid in EVA and the impurities in titanium dioxide will not corrode the battery cell, thereby strongly protecting the long-term reliability of the battery cell; (4) As a non-polar hydrophobic material, the POE material can improve the water barrier of the overall film and reduce the water vapor permeability of the film.
[0013] Preferably, the raw materials for preparing the first acid barrier layer and the second acid barrier layer independently include the following components in parts by weight:
[0014]
[0015] The raw materials for preparing the high reflective layer include the following components in parts by weight:
[0016]
[0017] Preferably, the raw materials for preparing the first acid barrier layer and the second acid barrier layer can be 90 parts, 91 parts, 92 parts, 93 parts, 94 parts, 95 parts, 96 parts, etc. in weight.
[0018] Preferably, the raw materials for preparing the first acid barrier layer and the second acid barrier layer may include 0.8 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, etc. of the cross-linking agent in parts by weight.
[0019] Preferably, the raw materials for preparing the first acid barrier layer and the second acid barrier layer are measured by weight, and the amount of silane used can be 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, etc.
[0020] Preferably, the amount of the light stabilizer used in the raw materials for preparing the first acid barrier layer and the second acid barrier layer can be 0.5 part, 0.6 part, 0.7 part, 0.8 part, 0.9 part, 1 part, etc., based on parts by weight.
[0021] Preferably, the raw materials for preparing the first acid barrier layer and the second acid barrier layer may include 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part, etc. of antioxidant in weight parts.
[0022] Preferably, the raw materials for preparing the high reflective layer are measured by weight, and the amount of EVA particles used can be 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts, 81 parts, 82 parts, 83 parts, 84 parts, 85 parts, etc.
[0023] Preferably, the raw materials for preparing the high reflective layer can be 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, etc. in weight.
[0024] Preferably, the amount of the cross-linking agent used in the preparation of the high reflective layer can be 0.8 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, etc., based on weight parts.
[0025] Preferably, the amount of silane used in the preparation of the high reflective layer can be 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.1 parts, 1.2 parts, 1.3 parts, 1.4 parts, 1.5 parts, etc., based on parts by weight.
[0026] Preferably, the amount of acrylate used in preparing the high reflective layer can be 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.1 parts, 1.2 parts, 1.3 parts, etc., based on parts by weight.
[0027] Preferably, the amount of the light stabilizer used in the preparation of the high reflective layer can be 0.1 part, 0.2 part, 0.3 part, 0.4 part, 0.5 part, 0.6 part, 0.7 part, etc., based on parts by weight.
[0028] Preferably, the amount of the antioxidant used in the preparation of the high reflective layer can be 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 part, etc., based on weight parts.
[0029] Preferably, the crosslinking agent includes any one of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, triallyl isocyanurate, triallyl cyanurate, diisopropylbenzene peroxide, benzoyl peroxide, di-tert-butyl peroxide or diisopropylbenzene hydroperoxide, or a combination of at least two thereof. That is, the crosslinking agents of the first acid barrier layer, the second acid barrier layer and the high reflective layer all include the above options.
[0030] Preferably, the silane includes any one or a combination of at least two of isocyanate propyl trioxyethyl silane, vinyl triacetoxy silane, methacryloxypropyl trimethoxy silane derivatives, small molecule polysiloxane or mercapto silane derivatives. That is, the silanes of the first acid barrier layer, the second acid barrier layer, and the high reflective layer all include the above options.
[0031] Preferably, the titanium dioxide includes rutile titanium dioxide, for example, any one of Longbai 886, Panhua DR-2588, and CITIC CR-210, or a combination of at least two thereof.
[0032] Preferably, the light stabilizer includes any one or a combination of at least two of a polymer of succinic acid and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol, bis-2,2,6,6-tetramethylpiperidinol sebacate, a hindered amine light stabilizer, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(2,4-di-tert-butylphenyl)phosphite or 2,2,6,6-tetramethyl-4-piperidinyl ester. That is, the light stabilizers of the first acid barrier layer, the second acid barrier layer and the high reflective layer all include the above selections.
[0033] Preferably, the antioxidant includes any one or a combination of at least two of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate or tris[2,4-di-tert-butylphenyl]phosphite. That is, the antioxidants of the first acid barrier layer, the second acid barrier layer and the high reflective layer all include the above selections.
[0034] Preferably, the acrylate includes any one of ethoxylated trimethylolpropane triacrylate, propoxylated trimethylol triacrylate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, polyethylene glycol diacrylate, tricyclohexane dimethanol diacrylate or ditrimethylolpropane tetraacrylate, or a combination of at least two thereof.
[0035] Preferably, the thickness of the first acid barrier layer and the second acid barrier layer are independently 100-150 μm, for example, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, etc.
[0036] Preferably, the thickness of the high reflective layer is 150-220 μm, for example, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, etc.
[0037] The present invention does not limit the preparation method of the white composite packaging film containing the acid barrier layer, and can be prepared by existing conventional methods. For example, through mixing, screw plasticization, die co-extrusion, and composite casting, the co-extruded white composite packaging film containing the acid barrier layer of the present invention can be obtained.
[0038] In a second aspect, the present invention provides a use of the white composite encapsulation film containing an acid barrier layer as described in the first aspect in a photovoltaic module.
[0039] Compared with the prior art, the present invention has the following beneficial effects:
[0040] The present invention adopts a specific structural design, wherein the middle layer is a high reflective layer, and the upper and lower layers are acid barrier layers. The raw materials and dosage of each layer are limited, so that the provided white composite packaging film has high reflectivity, high adhesion and can be maintained for a long time, and low water vapor permeability, and can also avoid the defects of the existing white EVA packaging film. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a schematic structural diagram of a white composite packaging adhesive film containing an acid barrier layer provided in Example 1 of the present invention.
[0042] Among them, 1 is the first acid barrier layer, 2 is the high reflection layer, and 3 is the second acid barrier layer. DETAILED DESCRIPTION
[0043] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0044] The information of some raw materials used in the examples and comparative examples of the present invention is as follows:
[0045] Mercaptosilane derivatives: J&Y M500, Shanghai Lanthanum Chemical Co., Ltd.
[0046] Small molecule polysiloxane: J&Y 550, Shanghai Lanthanum Chemical;
[0047] Methacryloyloxypropyltrimethoxysilane derivative: LA-570, Shanghai Lanthanum Chemical;
[0048] Polyethylene glycol diacrylate: Miyuan, MIRAMER M280;
[0049] Succinic acid, polymer with 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol: Light stabilizer 622, Xinxiu Chemical.
[0050] Example 1
[0051] In this embodiment, a white composite packaging film containing an acid barrier layer is provided, and its structural schematic diagram is shown as follows: Figure 1 As shown, the white composite packaging film containing an acid barrier layer comprises, from top to bottom, a first acid barrier layer 1, a high reflective layer 2, and a second acid barrier layer 3 which are stacked in sequence.
[0052] The thickness of the first acid barrier layer and the second acid barrier layer are both 120 μm, and the thickness of the high reflection layer is 200 μm.
[0053] The raw materials and amounts of the first acid barrier layer, the high reflective layer, and the second acid barrier layer are shown in Table 1:
[0054] Table 1
[0055]
[0056]
[0057] The preparation method comprises the following steps:
[0058] The raw materials for preparing the first acid barrier layer, the second acid barrier layer and the high reflective layer are blended separately, and then plasticized by a screw and co-extruded and cast by a die to obtain the white composite packaging film containing the acid barrier layer.
[0059] Example 2
[0060] In this embodiment, a white composite packaging film containing an acid barrier layer is provided. The white composite packaging film containing an acid barrier layer comprises a first acid barrier layer, a high reflective layer, and a second acid barrier layer stacked in sequence from top to bottom.
[0061] The thickness of the first acid barrier layer and the second acid barrier layer are both 120 μm, and the thickness of the high reflection layer is 200 μm.
[0062] The raw materials and amounts of the first acid barrier layer, the high reflective layer, and the second acid barrier layer are shown in Table 2:
[0063] Table 2
[0064]
[0065]
[0066] The preparation method is the same as Example 1.
[0067] Example 3
[0068] In this embodiment, a white composite packaging film containing an acid barrier layer is provided. The white composite packaging film containing an acid barrier layer comprises a first acid barrier layer, a high reflective layer, and a second acid barrier layer stacked in sequence from top to bottom.
[0069] The thickness of the first acid barrier layer and the second acid barrier layer are both 120 μm, and the thickness of the high reflection layer is 200 μm.
[0070] The raw materials and amounts of the first acid barrier layer, the high reflective layer, and the second acid barrier layer are shown in Table 3:
[0071] Table 3
[0072]
[0073]
[0074] The preparation method is the same as Example 1.
[0075] Example 4
[0076] In this embodiment, a white composite packaging film containing an acid barrier layer is provided. The white composite packaging film containing an acid barrier layer comprises a first acid barrier layer, a high reflective layer, and a second acid barrier layer stacked in sequence from top to bottom.
[0077] The thickness of the first acid barrier layer and the second acid barrier layer are both 120 μm, and the thickness of the high reflection layer is 200 μm.
[0078] The raw materials and amounts of the first acid barrier layer, the high reflective layer, and the second acid barrier layer are shown in Table 4:
[0079] Table 4
[0080]
[0081]
[0082] The preparation method is the same as Example 1.
[0083] Example 5
[0084] The only difference between this embodiment and embodiment 1 is that the silane in the first acid barrier layer and the second acid barrier layer is replaced by an equal amount of trimethylchlorosilane.
[0085] Example 6
[0086] The only difference between this embodiment and embodiment 1 is that the silane in the high reflective layer is replaced by an equal amount of trimethylchlorosilane.
[0087] Comparative Example 1
[0088] In this comparative example, a white encapsulating film is provided. The thickness of the white encapsulating film is 500 μm. The raw materials and dosages for preparation are shown in Table 5:
[0089] Table 5
[0090]
[0091] The steps include:
[0092] The raw materials in Table 5 were blended, plasticized by a screw, and co-extruded and cast by a die to obtain the white packaging film.
[0093] The performance test of the encapsulation films provided in the embodiments and comparative examples is carried out in the following manner:
[0094] (1) Water permeability: tested in accordance with ISO 15106-1:2003(E);
[0095] (2) Initial bonding strength with the back sheet: Test the flexible material against the rigid material in accordance with GB / T 2790-1995 Adhesive 180 peel strength test method;
[0096] (3) Bonding strength with back sheet after DH2000h: Test the flexible material against the rigid material according to GB / T 2790-1995 Adhesive 180 peel strength test method;
[0097] (4) Reflectivity: measured in accordance with HG / T 4915-2016 reflectivity of white reflective film;
[0098] (5) Δb (UV200h: tested in accordance with GB / T 29848-2018 Ethylene-vinyl acetate copolymer (EVA) film for photovoltaic module encapsulation materials;
[0099] (6) Δb (DH2000h): Tested in accordance with GB / T 29848-2018 Ethylene-vinyl acetate copolymer (EVA) adhesive film for photovoltaic module encapsulation materials;
[0100] (7) Acetic acid content (after cross-linking): tested according to ISO15106-1:2003(E)Plastics-Film and sheeting-Determination of water vapour transmission rate;
[0101] (8) Module power attenuation: The test is conducted in accordance with GB / T 29848-2018 Ethylene-vinyl acetate copolymer (EVA) film for photovoltaic module encapsulation materials.
[0102] The performance test results are shown in Table 6.
[0103] Table 6
[0104]
[0105]
[0106] It can be seen from Table 6 that the white composite packaging film containing an acid barrier layer provided by Examples 1-4 of the present invention has both high reflectivity and high adhesion and can be maintained for a long time (initial adhesion strength with the back sheet is 96.87-100.98 N / cm, and adhesion strength with the back sheet after DH2000h: 73.17-82.17 N / cm), and has a low water vapor transmission rate (15.96-16.93 g / m 2 .d).
[0107] Compared with the embodiment, the adhesive force of the white composite packaging film provided in Comparative Example 1 is poorer, and the water vapor transmission rate is also poorer.
[0108] In summary, the white composite encapsulation film containing an acid barrier layer does not reduce the reflectivity of the film. Compared with the conventional pre-cross-linked white EVA, the upper and lower acid barrier layers of the POE layer can improve the adhesion between the film and the glass, backplane, and battery cell and maintain it for a long time, thereby reducing the occurrence of component delamination during the aging process. Moreover, since the upper and lower layers of POE film do not contain acidic groups, the free acetic acid in EVA and the impurities in titanium dioxide will not corrode the battery cells, which strongly protects the long-term reliability of the battery cells. After aging, it has a lower yellowing index and component power attenuation, maintaining the long-term reliability of the component power. Moreover, the upper and lower layer materials, as non-polar hydrophobic materials, can improve the water barrier properties of the overall film, reduce the water vapor permeability of the film, and further improve the long-term reliability of the component.
[0109] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the white composite packaging film containing an acid barrier layer and its application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A white composite packaging film containing an acid barrier layer, characterized in that: The white composite packaging film containing an acid barrier layer comprises a first acid barrier layer, a high reflective layer, and a second acid barrier layer stacked in sequence from top to bottom; The raw materials for preparing the first acid barrier layer and the second acid barrier layer include the following components: POE particles, a crosslinking agent, silane, a light stabilizer and an antioxidant; The raw materials for preparing the high reflective layer include the following components: EVA particles, titanium dioxide, a crosslinking agent, silane, acrylate, a light stabilizer and an antioxidant.
2. The white composite packaging film containing an acid barrier layer according to claim 1, characterized in that: The raw materials for preparing the first acid barrier layer and the second acid barrier layer independently include the following components in parts by weight: The raw materials for preparing the high reflective layer include the following components in parts by weight:
3. The white composite packaging film containing an acid barrier layer according to claim 1 or 2, characterized in that: The crosslinking agent includes any one of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, triallyl isocyanurate, triallyl cyanurate, diisopropylbenzene peroxide, benzoyl peroxide, di-tert-butyl peroxide or diisopropylbenzene hydroperoxide, or a combination of at least two thereof.
4. The white composite packaging film containing an acid barrier layer according to any one of claims 1 to 3, characterized in that: The silane includes any one or a combination of at least two of isocyanate propyl trioxyethyl silane, vinyl triacetoxy silane, methacryloxypropyl trimethoxy silane derivatives, small molecule polysiloxane or mercapto silane derivatives.
5. The white composite packaging film containing an acid barrier layer according to any one of claims 1 to 4, characterized in that: The titanium dioxide includes rutile titanium dioxide.
6. The white composite packaging film containing an acid barrier layer according to any one of claims 1 to 5, characterized in that: The light stabilizer includes any one or a combination of at least two of a polymer of succinic acid and 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol, bis-2,2,6,6-tetramethylpiperidinol sebacate, a hindered amine light stabilizer, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(2,4-di-tert-butylphenyl) phosphite or 2,2,6,6-tetramethyl-4-piperidinyl ester.
7. The white composite packaging film containing an acid barrier layer according to any one of claims 1 to 6, characterized in that: The antioxidant includes any one of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate or tris[2,4-di-tert-butylphenyl]phosphite or a combination of at least two thereof.
8. The white composite packaging film containing an acid barrier layer according to any one of claims 1 to 7, characterized in that: The acrylate includes any one of ethoxylated trimethylolpropane triacrylate, propoxylated trimethylol triacrylate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, polyethylene glycol diacrylate, tricyclohexane dimethanol diacrylate or ditrimethylolpropane tetraacrylate, or a combination of at least two thereof.
9. The white composite packaging film containing an acid barrier layer according to any one of claims 1 to 8, characterized in that: The thickness of the first acid barrier layer and the second acid barrier layer are independently 100-150 μm; Preferably, the thickness of the high reflective layer is 150-220 μm.
10. Use of the white composite packaging film containing an acid barrier layer as claimed in any one of claims 1 to 9 in a photovoltaic module.